2016
DOI: 10.2174/1874325001610010757
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Satisfaction with Endoscopic Carpal Tunnel Releases and the Predictors - A Retrospective Cohort Study

Abstract: Background:Patient’s final satisfaction with endoscopic carpal tunnel release (ECTR) is still unpredictable. The study aims to find the predictive factors for satisfaction in patients with carpal tunnel syndrome (CTS) treated by ECTR using the Boston CTS questionnaire.Methods:We conducted a retrospective chart review of 37 patients (55 hands) who received ECTR and completed Boston carpal tunnel questionnaire at preoperative visit, 1 month and 6 months after operation while a telephone interview was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Gay et al found that the BCTQ is more sensitive to changes in clinical stats of patients than the electrophysiological findings, clinical examination or other generic questionnaires such as the Short-Form 36 and Disabilities of the Arm, Shoulder, and Hand questionnaire [12]. Some factors have been suggested as outcome predictors of carpal releasing surgery including age, gender, smoking, occupation, underlying disease, duration of symptoms, and preoperative muscle weakness or atrophy [7,8] However, in this study, most variables did not have a strong predictive value on patients' outcomes. In our study, patients with severe electrophysiological findings had higher postoperative FSS score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gay et al found that the BCTQ is more sensitive to changes in clinical stats of patients than the electrophysiological findings, clinical examination or other generic questionnaires such as the Short-Form 36 and Disabilities of the Arm, Shoulder, and Hand questionnaire [12]. Some factors have been suggested as outcome predictors of carpal releasing surgery including age, gender, smoking, occupation, underlying disease, duration of symptoms, and preoperative muscle weakness or atrophy [7,8] However, in this study, most variables did not have a strong predictive value on patients' outcomes. In our study, patients with severe electrophysiological findings had higher postoperative FSS score.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the Semmes-Weinstein monofilament test at the most prominent finger for each patient. Results were recorded by a 5-point scale as follows: 1-normal (2.83 monofilaments), 2-diminished light touch (3.61), 3diminished protective sensation (4.31), 4-loss of protective sensation (4.56), and 5-untestable sensation (6.65) [8]. Grip strength test was conducted using a Jamar dynamometer (Sammons Preston, Bolingbrook, Illinois) [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1998, Atroshi et al found higher age to be a risk factor for low patient reported satisfaction 6 months after OCTR in a study on 128 Swedish patients (mean age 51 years, range 21-94) [29]. On the contrary, a Taiwanese study including 58 patients (mean age 50.6 years, SD = 10.54) did not find a predictive effect of age on postoperative patient satisfaction [30]. The effect of age has also been examined with other outcomes such as return to work, disability, and symptom relief, with mixed findings showing no effect of age on return to work [31], QuickDASH improvement [12], or disability [32].…”
Section: Age and Gendermentioning
confidence: 97%
“…Chow[ 26 ] and Agee et al[ 27 ] reported that with the widespread use of endoscopic methods, new developments in endoscopic instruments and more experienced surgeons, the postoperative morbidity is decreased, the time until return to work after the surgery is shortened, and the scars are more cosmetic and painless. However, endoscopic techniques may also lead to high complication rates when performed without adequate knowledge of endoscopic anatomy and experience[ 15 , 18 , 28 ].…”
Section: Discussionmentioning
confidence: 99%